Assessing Carbon Pool Dynamics Under Coffee Agroforestry and Forest Management Systems - Aah Ahmad Almulqu; Melewanto Patabang (Jurnal Penelitian Pendidikan IPA, 2025)
Approximately 40.42 % of the forest in the province of East Nusa Tenggara is a protected forest, 23.68 % production forest, conservation forest 19.37 %, 10.90 % limited production forest and 5.63 % is convertible forest. Its still needs better management to optimize outcomes from these resources.  Analysis of dry forest composition, calculation of carbon pools availability, carbon sequestration and its behavior in East Nusa Tenggara, Indonesia are carried out to achieve these objectives.  The result shows that a total of 2097 tree individuals, it’s representing 94 species, 72 genera and 45 families, were found in the research sites.  Eucalyptus urophylla were found to be the most dominant species in the research sites and Elattostachys verrucosa have potential to replace Dryobalanops aromatic. Most of family distribution models can describe the stand structure in research sites. And carbon stock of the living, litter and soil all decreased from virgin forest to the conventional logging ang reduced impact logging, carbon concentration of these biomass in the coffea agroforestry system were slightly higher than those of virgin forest and logging treatments (ranging 0 – 52 %). Carbon stock of the living and soil increased with a decreasing harvest and reached the highest stock in the coffea agroforestry.